ANALISIS PENENTUAN BIAYA PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING UNTUK MENENTUKAN HARGA JUAL PADA PT. BLUE OCEAN GRACE INTERNATIONAL - Budiman, Jonathan Julio; Ilat, Ventje; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2019)
Company that focusing on creating profits, will definitely makes every effort to maintain the survival of its company. One of the ways to make more profit is to increase the selling price of its product. In carrying out the production process in order to produce a product that has a sale value,manufactures company will issue a variety of costs. These costs are classified into production emelents such as raw material cost,direct labor cost, and overhead factory cost. The purpose of this study is to apply the full costing method in order to set the selling price at the production cost. The analytical method that Â used in this study is qualitative with descriptive approach. The result of the study shows that the company in the way of setting the selling price indeed already calculating its production cost, but in calculating the factory overhead cost the company doesnâ€™t include the machine and equipment depreciation costs, component material cost, and insurance cost.